Integrasi Nilai-nilai Islam dalam Desain Pembelajaran Pendidikan Agama Islam: Kajian Tematik terhadap Ayat-ayat Al-Qur'an - Tuani Hot Parsaulian Tinambunan; Nur Khofifah; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning design in Islamic religious education plays a crucial role, as it focuses not only on mastering knowledge but also on the development of students' morals and spirituality. This study attempts to explain how Islamic values ​​can be integrated into the learning design process through a thematic study of verses from the Qur'an. This study employed a library research method with a thematic approach, examining verses from the Qur'an related to education and learning themes. The study found that verses such as QS Al-Baqarah: 31, QS An-Nahl: 125, and QS Ali-Imran: 159 contain educational principles relevant to learning design, including careful planning, wisdom in delivery, and compassion in educating. These values ​​align with the principles of modern, learner-oriented learning design. Therefore, the integration of Qur'anic values ​​into Islamic religious learning design serves as an important foundation for creating a holistic and Islamic learning process